A postcolonial analysis of Cuban foreign policy towards South African liberation movements, 1959-1994 - Sarmiento, Oddveig Nicole (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.